FERMENTASI KOTORAN KAMBING DAN AYAM DENGAN NIRA LONTAR SEBAGAI PAKAN AYAM - . Helda; Cytske Sabuna (Politeknik Pertanian Negeri Kupang, 2012)
Goat and Chicken Fecal Fermentation with Lontar Sap as Chicken Feed. The effect of goat faces and chicken faces on the chemical characteristic and production performance of native chicken were investigated. The experiment was conducted in two parts. In the first parts, goat faces and chicken faces were fermented with different level of palm tree sap. In the second experiment, the feeding value of fermented goat faces and chicken faces was evaluated. Both experiments were conducted as a complete randomized design consisting of four treatments. The level of palm tree nira used in the first experiment was 0, 5, 10 and 15% respectively. The diets, in mash form, were fed ad libitum to four pens of ten mix native chicken each from week 12 to 16 post-hatch. ?????? The result showed that as the level of nira lontar increased, the chemical composition of fermented goat faces and chicken faces increased. Excluding feed consumption, the production performance of birds fed diets containing different level of fermented goat faces and chicken faces was similar (P>0,05) to that of control dietKey word: fermentation, goat faces, and chicken faces, native chicken